Easy construction of furo[2, 3-f]isoindole core by the IMDAV reaction between 3-(furyl)allylamines and α, β-unsaturated acid anhydrides. Issue 18 (5th May 2016) - Zubkov, Fedor I.; Zaytsev, Vladimir P.; Mertsalov, Dmitriy F.; Nikitina, Eugenia V.; Horak, Yuriy I.; Lytvyn, Roman Z.; Homza, Yuriy V.; Obushak, Mykola D.; Dorovatovskii, Pavel V.; Khrustalev, Victor N.; Varlamov, Alexey V.
Abstract: The vinylogues of furfurylamines, easily available in two steps from furylacroleins (3-(furyl)allylamines), were studied in a tandem N-acylation/intramolecular [4+2] cycloaddition with maleic, pyrocinchonic, and citraconic anhydrides, as well as furylacryloyl and cinnamoyl chlorides. By using a domino reaction of 3-(furyl)allylamines and α, β-unsaturated acid anhydrides under mild conditions, various hexahydro-4 H -furo[2, 3- f ]isoindoles and their carboxyl derivatives were synthesized efficiently. The domino sequence includes three steps: acylation of the nitrogen atom in 3-(furyl)allylamines, intramolecular Diels–Alder cycloaddition in the resulting N -acyl vinylfurans (IMDAV reaction), and prototropic shift of the adducts followed by recovery of aromaticity of the furan nucleus. The key step, IMDAV reaction, leads to the target products, furo[2, 3- f ]isoindoles, diastereoselectively and with relatively high yields. Graphical abstract: